Talking and thinking with AI - Centa Strahovnik, Mateja (Poligrafi, 2025)
The incorporation of large language models or ai-driven chatbots into every-day communication and knowledge practices has significant implications for how we think and understand ourselves as epistemic agents. This paper investigates how ai chatbots reshape epistemic identity and virtue, focusing on the effects of human-ai interaction. The use of ai chatbots can ultimately impact epistemic virtues such as curiosity, intellectual humility, and open-mindedness on the one hand, and also raise questions about epistemic agency and responsibility on the other. This paper emphasizes the importance of reflective practices that maintain human autonomy, foster epistemic responsibility, and promote virtuous collabo-ration with ai systems. Ultimately, this paper advocates for a partial reimagining of epistemic identity and epistemic collaboration in the age of ai, seeking a bal-ance between the advantages of ai and the significance and uniqueness of human intellectual endeavors.
Keywords: agency; artificial intelligence (AI); delovanje; epistemic collaboration; epistemic identity; epistemic virtue; human-AI interaction; interakcija med človekom in UI; spoznavna identiteta; spoznavne vrline; spoznavno sodelovanje; umetna inteligenca (UI)